Autonomous and non‐autonomous functions of the maize Shohai1 gene, encoding a RWP‐RK putative transcription factor, in regulation of embryo and endosperm development. (20th July 2018) - Mimura, Manaki; Kudo, Toru; Wu, Shan; McCarty, Donald R.; Suzuki, Masaharu
Summary: In plants, establishment of the basic body plan during embryogenesis involves complex processes of axis formation, cell fate specification and organ differentiation. While molecular mechanisms of embryogenesis have been well studied in the eudicot Arabidopsis, only a small number of genes regulating embryogenesis has been identified in grass species. Here, we show that a RKD‐type RWP‐RK transcription factor encoded by Shohai1 ( Shai1 ) is indispensable for embryo and endosperm development in maize. Loss of Shai1 function causes variable morphological defects in the embryo including small scutellum, shoot axis bifurcation and arrest during early organogenesis. Analysis of molecular markers in mutant embryos reveals disturbed patterning of gene expression and altered polar auxin transport. In contrast with typical embryo‐defective ( emb ) mutants that expose a vacant embryo pocket in the endosperm, the endosperm of shai1 kernels conforms to the varied size and shape of the embryo. Furthermore, genetic analysis confirms that Shai1 is required for autonomous formation of the embryo pocket in endosperm of emb mutants. Analyses of genetic mosaic kernels generated by B–A translocation revealed that expression of Shai1 in the endosperm could partially rescue a shai1 mutant embryo and suggested that Shai1 is involved in non‐cell autonomous signaling from endosperm that supports normal embryo growth. Taken together, we propose that the Shai1 gene functions in regulating embryonic patterning during grass embryogenesis partly by endosperm‐to‐embryo interaction. Significance Statement: Whereas understanding of embryogenesis establishing basic body plans of plants and animals is a fundamental theme in biology, genetic mechanisms of grass embryogenesis are little understood in plants. Here, we identify Shohai1, encoding a RWP‐RK domain putative transcription factor, as an important gene of maize embryogenesis, and demonstrate that Shohai1 promotes apical‐basal embryo polarization at least partly through endosperm via an organ non‐autonomous mechanism.